Physical effect of air pollution on leave and bark surface near cement plant in perlis - Rurynee Bt Roslan (School of Environmental Engineering University Malaysia Perlis, 2011)
Air pollution is one of the major problems since it is effect the health of occupant and nearby residential of cement plant. Perlis is one of the lowest rates of air pollution . Even though it is the lowest rate, it should be consider to prevent air pollution and to overcome more clean air in the future. The purpose of this study are to study the use of SEM & EDX method on leave and bark surface for air pollution distribution , to investigate the physical effect of cement plant emission to surrounding , and to determine the comparison between (SEM/EDX) is used to measure air pollutant near to the cement plant in Bukit Keteri, Chuping, Perlis. An energy dispersive X-ray microanalyzer (EDX) connected to a scanning electron microscopic (SEM) was used to measure the amount of several elements on the leave and bark surface.